Genetic types, origins, and accumulation process of natural gas from the southwestern Junggar Basin: New implications for natural gas exploration potential. (January 2021) - Zhi, Dongming; Song, Yong; Zheng, Menglin; Qin, Zhijun; Gong, Deyu
Abstract: Although the Junggar Basin is one of the four largest petroliferous basins in China, the proved reserves of natural gas is primarily concentrated in the eastern and southern parts of the basin and only account for 9.0% of the total resources. In this study, four types of natural gas are identified in the southwestern Junggar Basin based on their molecular composition, stable carbon isotopes, and low molecular weight hydrocarbons. Type I gas is coal-type gas generated from highly mature–overmature humic source rocks of the deeply buried Carboniferous (C)–Lower Permian Jiamuhe Formation (P1 j) in the Shawan Sag. Type II gas is derived from lacustrine source rocks of the Lower Permian Fengcheng Formation (P1 f), which can be further divided into the two subtypes IIA and IIB . The former is highly mature oil-type gas from the Shawan Sag, while the latter is low-mature oil-type gas from the Mahu Sag. Type III gas is a mixture of Types I and II gases. Type IV gas is secondary microbial gas formed by the biodegradation of oils. The ethane and propane are systematically affected by biodegradation, and the selective biodegradation of propane is most notable. Based on the results of reservoir fluid inclusions and the reconstructed burial and thermal histories, two stages of oil and gas charging events and one stage of oil and gas adjustment are identified in the study area. The first stage of oil and gas charging event occurred from the Late Triassic to the Early Jurassic in terms of the homogenization temperatures of 70–100 °C of hydrocarbon inclusions. During this stage, hydrocarbons generated from P1 j/C and P1 f source rocks in the Shawan Sag migrated along faults and unconformities to structural highs and accumulated in reservoirs. In the Late Jurassic, a large-scale uplifting event occurred, and the early natural gas was extensively lost and the oils suffered severe biodegradation, leading to the formation of a large amount of secondary microbial methane. The second charging event occurred during the Early Cretaceous based on the homogenization temperature of hydrocarbon inclusions ( 100–125 °C). At this stage, the study area began to subside again and large amounts of highly mature coal-type and oil-type gases were generated from the P1 f and P1 j/C source rocks, which migrated to structural highs to form new gas pools. These results confirm that there are two sets of effective gas source rocks i.e., C/P1 j and P1 f, in the southwestern Junggar Basin, revealing a new field for natural gas exploration. The results of this study represent a case study regarding the gas–source correlation and restoration of the accumulation process under complex geological conditions and improve the understanding of the natural gas exploration potential in the Junggar Basin. Highlights: The Permian oil-type gas becomes a new exploration field in the Junggar Basin. The C/P1 j-related coal-type gas system is developed in the SW Junggar Basin. Secondary microbial methane is a potential gas resource and widely distributed. Two significant oil and gas charging periods occurred in the SW Junggar Basin. One significant stage of oil and gas adjustment occurred in the Late Jurassic.